Effects of vitamin D supplementation on maximal strength and power in athletes: a systematic review and meta-analysis of randomized controlled trials - Sist, Marco; Zou, Lu; Galloway, Stuart D. R.; Rodriguez-Sanchez, Nidia (Frontiers in Nutrition, 2023)
Vitamin D is thought to be a powerful modulator of skeletal muscle physiology. However, available data on the effects of vitamin D supplementation on muscle function in athletes are limited and with mixed results. This meta-analysis therefore, aimed to quantitatively summarize the up-to-date literature assessing the effects of vitamin D supplementation on muscle strength and power in athletes.Sport Discus, PubMed, Cochrane Library and Web of Science were searched to identify randomized controlled trials (RCTs) that used one-repetition maximum (1RM) tests to assess maximal strength, and vertical jump to assess muscle power in athletes. The Cochrane Risk of Bias tool was used to evaluate the included RCTs for sources of bias. The standardized mean difference (SMD) was used as the effect size, interpreted together with its 95% confidence intervals (CI). The effect sizes were calculated on the changes from baseline between vitamin D and placebo groups for maximal strength results by upper body and lower body, and for power results.Eleven RCTs involving 436 athletes were included. The results indicated that if baseline serum 25(OH)D concentration was <75 nmol/L, the treatment had a small effect on upper body muscle strength [SMD 0.25, 95% CI: (-0.44, 0.95), p=0.47] and on lower body muscle strength [SMD 0.26, 95% CI: (-0.13, 0.65), p=0.19]; if the baseline serum 25(OH)D concentration was ≥75 nmol/L, the treatment had a trivial effect on muscle power [SMD 0.15, 95% CI: (-0.42, 0.72), p=0.61].